Financial Attitude Research: A Systematic Literature Review and Bibliometric Analysis - Muhammad Ali Sa’id (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
In recent decades, financial attitude has increasingly been recognized as a key construct in explaining individuals’ financial management behavior and financial well-being. Despite the growing volume of studies on financial attitude, the existing literature remains fragmented across disciplines, contexts, and methodological approaches, thereby necessitating a systematic and comprehensive synthesis. This study aims to map the development, distribution, and intellectual structure of financial attitude research, while also assessing its relevance and implications for future research agendas and financial policy. This study employs a Systematic Literature Review (SLR) combined with bibliometric analysis of Scopus-indexed articles published up to December 16, 2025. The literature selection process followed the PRISMA guidelines and resulted in 197 open-access articles, which were analyzed using VOSviewer to identify publication trends, collaboration patterns, and keyword networks. The findings indicate that financial attitude research has experienced substantial growth over the past decade and has evolved into a globally distributed and strongly interdisciplinary field. Keyword co-occurrence analysis reveals that financial attitude serves as a central conceptual node linking financial literacy, financial knowledge and skills, financial behaviour, and financial well-being. These results underscore the role of financial attitude as a critical mechanism bridging cognitive and behavioral dimensions in financial decision-making, with significant theoretical and practical implications for behavioral finance models, financial literacy policies, and interventions aimed at improving financial well-being. This study contributes by providing a comprehensive intellectual map of financial attitude research and by identifying future research opportunities across individual, social, and institutional contexts.